A simulation-based multi-objective optimization study of the fleet sizing problem in the offshore industry. Issue 4 (December 2016) - Eskandari, Hamidreza; Mahmoodi, Ehsan
Abstract Oil companies usually hire a number of offshore supply vessels (OSVs) under long-term contracts for offshore supply logistics. If the number of long-term chartered vessels is not sufficient to satisfy platform demands, one or more OSVs would be required under short-term contracts. In this article two policies for OSV routing to installations are compared: routing based on a fixed schedule, currently used in Iranian offshore oil company and routing based on platform demands. A discrete-event simulation model is developed and simulation-based optimization is used to find near-optimal fleet size and composition that minimize expected total cost subject to a minimum desired expected platform service level. Changing the platform service level constraint allows results to be obtained for multiple best compromise solutions along a performance trade-off curve. For each routing policy, an optimal trade-off curve is obtained using simulation-based optimization. Performance evaluation of routing policies is compared at different service levels. Experimental results indicate that the routing based on platform demands dominates the routing based on a fixed schedule under near-optimal decision variable settings.